The Effect Of Gasket Thickness Variations (Packing Block) On Power, Torque & Engine Rotation Of Yamaha F1ZR - Iqbal Risfianda Arraihan; Bambang Sudarsono (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
This study analyzes the effect of gasket thickness on motorcycle engine performance, focusing on its role in maintaining pressure and temperature within the engine, which directly influences efficiency and power output. Employing a descriptive quantitative and qualitative approach, including in-depth interviews with mechanics, racers, and engine experts, the research explores the impact of gasket thickness on engine power, fuel efficiency, and durability under various conditions. Thematic analysis of the data reveals that thinner gaskets enhance power but compromise long-term durability, offering valuable insights for practitioners and manufacturers in optimizing gasket thickness for high-performance applications.